Preparation method of organ-shaped MXene and one-dimensional WO3 nanorod nano self-reduction growth Au nanoparticle NO2 gas-sensitive composite material

Through the preparation of a composite material of organ-like Ti3C2Tx and one-dimensional WO3 nanorods and Au nanoparticles, the problem of low response and temperature dependence of WO3 gas-sensitive sensors to NO2 in the prior art is solved, and high sensitivity NO2 detection at room temperature is achieved.

CN119800302APending Publication Date: 2025-04-11CHANGCHUN UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311303360.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the gas sensor based on one-dimensional WO3 has a relatively low gas-sensitive response to NO2, and the detection lower limit can generally only reach the ppm level, and can only operate at higher temperatures.

Method used

The organ-like Ti3C2Tx is used as the substrate, combining high-performance one-dimensional WO3 nanorods with excellent structure and Au nanoparticles that can improve oxygen vacancy, and MXene/WO3/Au nanocomposites are prepared by hydrothermal method and self-reduction method. The material has mesoporability, large specific surface area, good chemical stability and high sensitivity.

Benefits of technology

It realizes gas-sensitive detection of NO2 at room temperature with high sensitivity, low detection lower limit and high selectivity. The response can reach 3.97 at room temperature, and has good repeatability, fast response and good chemical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800302A_ABST
    Figure CN119800302A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an organ-shaped MXene and one-dimensional WO3 nanorod nano self-reduction growth Au nanoparticle NO2 gas-sensitive composite material. The preparation method comprises the following specific steps: (1) preparing a high-molecular flexible substrate; (2) preparation of organ-shaped MXene; (3) preparing an MXene / WO3 composite material; and (4) preparation of an MXene / WO3 / Au composite material: the adding mass of accordion-shaped MXene is 5-160 mg, the adding amount of tetrachloroauric acid (HAuCl4. 3H2O) is 30 [mu] L, the product obtained by reaction is the MXene / WO3 / Au composite material, and the flexible substrate on which the composite gas sensitive material is deposited is the prepared NO2 sensor. The organ-shaped MXene and one-dimensional WO3 nanorod self-reduction growth Au nanoparticle NO2 gas-sensitive composite material prepared by the invention has a uniformly dispersed composite structure, the introduction of the organ-shaped MXene effectively improves the conductivity of WO3, and meanwhile, rich functional groups on the surface of the composite material contribute to improving the gas-sensitive property of WO3. Different electrodes can be deposited on the flexible substrate, the cost is low, the steps are simple and controllable, the flexibility is good, the sensitivity is high, and NO2 detection can be realized at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of MXene preparation, and in particular to an accordion-shaped Ti3C2T x The invention relates to a composite material of Au nanoparticles grown by self-reduction of one-dimensional WO3 nanorods and a preparation method and application thereof. The accordion-shaped MXene is prepared by acid etching with MAX phase Ti3AlC2 as a precursor, and a novel nano-gas-sensitive composite material MXene / WO3 / Au is prepared by hydrothermal method and self-reduction method with accordion-shaped MXene, sodium tungstate dihydrate, thioacetamide and tetrachloroauric acid as monomers. This nano-composite material can be used as a room temperature gas-sensitive sensing material for sensitive detection of NO2 gas in mixed gases, and belongs to the technical field of nano-composite functional gas-sensitive materials. Background Art

[0002] Room temperature monitoring of harmful gases represented by volatile organic compounds (VOCs) and air pollutants (NO2, SO2, NH3, H2S, etc.) has attracted widespread attention. Among them, nitrogen dioxide (NO2) is a reddish-brown toxic gas with a pungent smell; it is a harmful gas produced in cooking, combustion in factories and thermal power plants, and automobile emissions. When the concentration of NO2 in the atmosphere is too high, it will cause acid rain and photochemical smog. According to research, exposure to low concentrations of NO2 (about 3 ppm) will have an irritating effect on the human respiratory system, while exposure to higher concentrations of NO2 will cause human poisoning, respiratory diseases, cancer, abnormal lung function and even death. Therefore, for the sake of human health and environmental monitoring, it is very necessary and practical to study and invent a highly responsive, highly sensitive and stable NO2 room temperature gas-sensitive material.

[0003] So far, a variety of gas-sensitive detection materials have been studied, such as organic polymer materials, metal oxide materials, graphene materials, and MOF materials. Electrical (resistance) metal oxide semiconductor gas sensors (MOS) have been widely used due to the advantages of adjustable metal oxide size, simple operation, easy manufacturing, and low cost. Nano-metal oxide WO3 is very suitable for the detection of NO2 gas because of its high surface area and simple sensing mechanism. However, the gas-sensitive response of gas sensors based on one-dimensional original WO3 to NO2 is relatively low, and the detection limit can generally only reach the ppm level, and can only work at higher temperatures.

[0004] Obviously, the method of constructing heterostructures and composite materials using accordion-shaped MXene and Au nanoparticles should be able to improve the gas sensing performance of one-dimensional WO3. It not only retains the sensing characteristics and stability of the oxide semiconductor material itself, but also gives the material good selection specificity, low detection limit, high sensitivity, repeatability and the possibility of working at room temperature, providing a new idea for detecting NO2 in room temperature environment. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a new type of MXene semiconductor oxide (abbreviated as MXene / WO3 / Au) composite material containing rich surface groups, microporosity, large specific surface area, uniform particle size, good chemical stability and good electrical conductivity in view of the shortcomings and defects mentioned in the background technology, and provide a preparation method and application of the nanocomposite material. The nanocomposite material can achieve room temperature sensing detection of NO2 with high sensitivity, low detection limit and high selectivity at room temperature.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: Ti3C2T x / WO3 / Au nanocomposite material, using a unique accordion-like structure with low cost and a two-dimensional graphene-like material Ti3C2T with high specific area and good electron transport ability x It is a substrate and one-dimensional WO3 nanorods with excellent structure and high performance, as well as Au particles that can improve oxygen vacancies.

[0007] As shown in the figure, the nanocomposite material is generally accordion-shaped, with a gap between material layers of 130-160 nm; it has mesoporous properties and a high specific surface area of ​​84.469 m 2 g -1 , providing a large number of active adsorption sites for gas adsorption. The one-dimensional WO3 nanorods with a diameter of 60~80 nm and Au particles with a particle size of 30~40 nm are distributed on the surface, which provides the material with excellent selectivity and low detection limit.

[0008] As a general inventive concept, another aspect of the present invention provides a method for preparing the above-mentioned MXene / WO3 / Au high-performance nanocomposite material, comprising the following steps: (1) Preparation of polymer flexible substrate: After cutting the flexible nylon substrate, ultrasonically clean it with deionized water, acetone and ethanol respectively. After drying the substrate with nitrogen, magnetron sputtering technology is used to sputter interdigitated electrodes on the substrate through the engraved template for future use.

[0009] (2) Preparation of MXene / WO3 / Au nanocomposites: Using MAX phase Ti3AlC2 as precursor, accordion-shaped MXene as substrate, sodium tungstate dihydrate (Na2WO4·2H2O) and thioacetamide (CH3CSNH2) as raw materials, a simple and efficient hydrothermal method was used to synthesize Ti3C2Tx / WO3 nanocomposites under acidic conditions (HCL (37% in H2O)). The prepared MXene / WO3 composite material was used as a framework to uniformly load Au nanoparticles via a self-reduction reaction to obtain a MXene / WO3 / Au composite material.

[0010] Preferably, the above preparation method specifically comprises the following steps: Step (1) Preparation of polymer flexible substrate: Cut the flexible nylon substrate into a length of 15 mm and a width of 15 mm, and ultrasonically clean it with deionized water, acetone and ethanol respectively, with an ultrasonic frequency of 30-50 KHz and an ultrasonic cleaning time of 5-15 min. After the substrate is blown dry with nitrogen, a magnetron sputtering technique is used to sputter a 10 mm long and 1 mm wide interdigitated electrode onto the substrate through an engraved template, which is then set aside for use.

[0011] Step (2) Preparation of accordion-shaped MXene: 1-2 g of the precursor MAX phase is placed in a cylindrical reactor with a lid made of polytetrafluoroethylene. In order to remove the H2 produced during the reaction, which may cause safety hazards, a 5 mm diameter exhaust hole is opened 1 cm away from the top of the reactor using a punching machine. Before adding the precursor material MAX phase, in order to prevent the reaction from being too violent when hydrofluoric acid (HF (38% in H2O)) is directly added and to solve the problem of incomplete acid etching. Place 20-40 mL of 3-12 mol / L hydrofluoric acid (HF (38% in H2O)) in an open-pore polytetrafluoroethylene reactor, stabilize the liquid environment temperature at 0-10 °C by adding ice cubes into a constant temperature water bath, immerse the reactor in a constant temperature water bath, add a magnetic stirrer and stir at 500 r / min-1000 r / min for 1-10 minutes, then divide the precursor MAX phase into multiple portions, slowly add them to the reactor in sequence, set the constant temperature water bath to 30-60 °C, react for 12-48 h, and prepare accordion-shaped MXene. After the reaction, place the obtained suspension in a centrifuge tube and use deionized water to centrifuge and wash multiple times at 3500 rpm-10000 rpm until the pH is equal to 7, and then place it in a freeze dryer for freeze drying for 24 h-48 h.

[0012] Step (3) Preparation of MXene / WO3 composite material: 0.1-2 g sodium tungstate dihydrate (Na2WO4·2H2O) and 0.1-2 g thioacetamide (CH3CSNH2) are placed in a beaker, deionized water is added, and magnetic stirring is performed at 500 r / min-1000 r / min for 2 hours to obtain a stable dispersion. The dispersion is mixed and stirred in the beaker for 1 hour, and the accordion-shaped MXene prepared in step (2) is stirred with the solution for 10 minutes. The mass percentage of the added accordion-shaped MXene is 5.0 mg-160 mg. 3-12 mol / L hydrochloric acid (HCL (37% in H2O)) is used to titrate the pH to 2-5, and then the solution is placed in a hydrothermal reactor made of polytetrafluoroethylene and placed in an oven to react at 100-200 °C for 10-20 hours.

[0013] Step (4) Preparation of MXene / WO3 / Au composite material: After the reaction is completed, the suspension obtained in step (3) is placed in a centrifuge tube and repeatedly centrifuged and washed with deionized water at 3500 rpm to 10000 rpm, and then placed in a freeze dryer for freeze drying for 24 h to 48 h to obtain a MXene / WO3 composite material. 10-100 mg of freeze-dried powder MXene / WO3 was ultrasonically dispersed in 50-100 μL of deionized water at an ultrasonic frequency of 30-50 KHz for 0.5-1.5 h, and 0.01-1 mL of 0.1 mol / L tetrachloroauric acid (HAuCl4·3H2O) was slowly added for self-reduction reaction for 5-60 min. The mixture was placed in a freeze dryer and dried for 12-48 h to obtain a MXene / WO3 / Au composite material. 5-20 mg of the composite material obtained in step (4) was dispersed in 50-200 μL of deionized water, and the mixture was drop-casted onto the substrate obtained in step (1) using a pipette using a solid solution drop-casting method and naturally dried.

[0014] In the above preparation method, preferably, in the step (4), the centrifugal speed is 3500 rpm, the freeze-drying time is 24 h, the freeze-dried powder MXene / WO3 is added in an amount of 100 mg and dispersed in 100 mL of deionized water, ultrasonically dispersed at an ultrasonic frequency of 40 KHz for 0.5 h, 0.03 mL of 0.1 mol / L tetrachloroauric acid (HAuCl4·3H2O) is slowly added dropwise, the self-reduction reaction is carried out for 5 min, and the mixture is placed in a freeze dryer for freeze drying for 24 h, 10 mg of the MXene / WO3 / Au composite material is dispersed in 50 μL of deionized water, transferred to the flexible substrate obtained in step (1), and naturally dried for 24 h.

[0015] In the above preparation method, preferably, in the step (3), sodium tungstate dihydrate (Na2WO4·2H2O) and thioacetamide (CH3CSNH2) accordion-shaped MXene, the added amount of sodium tungstate dihydrate (Na2WO4·2H2O) is 1 g, the added amount of thioacetamide (CH3CSNH2) is 0.6 g, and the added mass of the accordion-shaped MXene is 20 mg.

[0016] In the above preparation method, preferably, the accordion-shaped MXene added in step (3) is one of Ti3C2, Ti2C, Nb3C4, Nb2C, V3C2, V2C, Ta4C3, Ta2C and Mo2C.

[0017] In the above preparation method, preferably, in step (3), 12 mol / L hydrochloric acid (Hcl (37% inH2O)) is slowly titrated until the pH value of the solution reaches 3.

[0018] In the above preparation method, preferably, in step (3), the hydrothermal reaction kettle made of polytetrafluoroethylene is placed in an oven and reacted at 200° C. for 20 h.

[0019] In the above preparation method, preferably, in the step (2), the MAX phase material is one of Ti3AlC2, Ti2AlC, Nb3AlC4, Nb2AlC, V3AlC2, V2AlC, Ta4AlC3, Ta2AlC and Mo2AlC.

[0020] In the above preparation method, preferably, in the step (2), 2 g of the MAX phase material is slowly added multiple times and dissolved in 40 mL of 3-12 mol / L hydrofluoric acid (HF (38% in H2O)), and a constant temperature water bath is set at 40°C for reaction for 36 h. After the reaction, the obtained suspension is placed in a centrifuge tube and centrifuged and washed multiple times with deionized water at 3500 rpm until the pH is equal to 7, and then placed in a freeze dryer for freeze drying for 24 h.

[0021] In the above preparation method, preferably, before adding the MAX phase material to HF in step (2), the liquid environment temperature is stabilized at 5°C by adding ice cubes to a constant temperature water bath, and the reactor is immersed in a constant temperature water bath, a magnetic stirrer is added, and stirred at 500 r / min for 5 minutes.

[0022] In the above preparation method, preferably, in the step (1), the nylon substrate is cut into a length of 15 mm and a width of 15 mm, the ultrasonic washing is performed at an ultrasonic frequency of 40 KHz and a ultrasonic washing time of 10 min, and after the substrate is blown dry with nitrogen for 5 min, a magnetron sputtering technique is used to sputter an interdigitated electrode with a length of 10 mm and a width of 1 mm onto the substrate through an engraved template, and the electrode is set aside for use.

[0023] The present invention also provides an application, wherein the Ti3C2T x / WO3 / Au nanocomposite materials are used as room temperature gas sensitive sensing materials, mainly for detecting NO2 in mixed gases.

[0024] The technical effects of the present invention are: Compared with the prior art, the MXene / WO3 / Au composite material provided by the present invention has mesoporosity, a large specific surface area, a large interlayer spacing, good chemical stability and high sensitivity, and can be used as a gas sensor for high-sensitivity and high-selectivity gas-sensitive detection of NO2 in mixed gases. On the one hand, MXene has an accordion-like geometric structure. The introduction of MXene can provide a large number of gas adsorption sites due to its large interlayer gap. At the same time, its rich functional groups on the surface help to improve the gas sensing performance of one-dimensional WO3 nanorods. MXene / WO3 has a three-dimensional structure. Because tungsten oxide (WO3) is an n-type semiconductor with a band gap of 2.6~2.8 eV, a large number of intrinsic oxygen vacancy defects, and excellent thermal stability and chemical stability and good electron transport capacity that are beneficial to gas sensing applications; on the other hand, the formed mesoporous structure is conducive to the adsorption and diffusion of gases; at the same time, the introduction of Au nanoparticles evenly distributed on the surface of the material further improves the oxygen vacancies of the nanocomposite material, making it have more excellent gas-sensitive properties without the need for any heating conditions. Therefore, high-sensitivity detection of NO2 can be achieved at room temperature, and the responsivity can reach 3.97 at room temperature (25 °C), with good repeatability, fast response, and good chemical stability.

[0025] By depositing MXene / WO3 / Au nanocomposite materials onto cheap polymer flexible substrates, a flexible room-temperature NO2 sensor with high sensitivity based on the composite sensitive material was obtained. Different electrodes can be deposited on the flexible substrate, which has low cost, simple and controllable steps, good flexibility, high sensitivity, can detect NO2 at room temperature, and has great potential for application in people's real life. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0027] Figure 1 This is a SEM image of the MXene / WO3 / Au composite gas-sensitive material prepared in Example 1 of the present invention.

[0028] Figure 2 It is a SEM image of MXene / WO3 prepared in Comparative Example 1 of the present invention.

[0029] Figure 3 It is a SEM picture of WO3 prepared in Comparative Example 2 of the present invention.

[0030] Figure 4 1 ppm NO2 sensitivity of the sensors prepared by Examples 1-2 of the present invention and Comparative Example 1 and Comparative Example 2.

[0031] Figure 5 This is a response curve of the sensor prepared in Example 3 of the present invention to 200 ppb~1 ppm NO2. Implementation

[0032] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical scheme of the present invention is now described in detail below in conjunction with specific embodiments. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Example

[0033] A preparation method of an accordion-shaped MXene and one-dimensional WO3 nanorod nano self-reduction growth Au nanoparticle NO2 gas-sensitive composite material, the specific method is as follows: (1) The flexible nylon substrate was cut into pieces with a length of 15 mm and a width of 15 mm. The pieces were ultrasonically cleaned with deionized water, acetone, and ethanol, respectively, at an ultrasonic frequency of 40 kHz and for 10 min. The substrate was blown dry with nitrogen for 5 min, and then magnetron sputtering technology was used to sputter interdigital electrodes with a length of 10 mm and a width of 1 mm onto the substrate through the engraved template. The electrodes were set aside for later use.

[0034] (2) 2 g of the precursor MAX phase was placed in a cylindrical polytetrafluoroethylene reactor with a lid and a 5 mm vent hole. Before adding the precursor material MAX phase, in order to prevent the reaction from being too violent when hydrofluoric acid (HF (38% in H2O)) is directly added and to solve the problem of incomplete acid etching. 20 mL of 12 mol / L hydrofluoric acid (HF (38% in H2O)) was first placed in an open-pore polytetrafluoroethylene reactor. Ice cubes were added to the constant temperature water bath to stabilize the liquid environment temperature at 5°C. The reactor was immersed in a constant temperature water bath and a magnetic stirrer was added. After stirring at 500 r / min for 5 minutes, the precursor MAX phase was divided into multiple portions and slowly added to the reactor in sequence. The constant temperature water bath was then set to 40°C and reacted for 36 h to prepare accordion-shaped MXene. After the reaction, the obtained suspension was placed in a centrifuge tube and washed with deionized water at 3500 rpm for multiple times until the pH was equal to 7, and then placed in a freeze dryer for freeze drying for 24 h.

[0035] (3) 1 g of sodium tungstate dihydrate (Na2WO4·2H2O) and 0.6 g of thioacetamide (CH3CSNH2) were placed in a beaker, 10 mL of deionized water was added, and the mixture was stirred under magnetic stirring at 500 r / min for 2 hours to obtain a stable dispersion. The dispersion was mixed and stirred in the beaker for 1 hour, and then 5 mg of the prepared accordion-shaped MXene was stirred with the solution for 10 minutes. The pH was then titrated to 3 using 12 mol / L hydrochloric acid (Hcl (37% in H2O)), and the solution was placed in a polytetrafluoroethylene hydrothermal reactor and placed in an oven to react at 200°C for 20 hours.

[0036] (4) 100 mg of freeze-dried powder MXene / WO3 was ultrasonically dispersed in 50 μL of deionized water at an ultrasonic frequency of 40 kHz for 0.5 h. 30 μL of 0.1 mol / L tetrachloroauric acid (HAuCl4·3H2O) was slowly added for self-reduction reaction for 5 min. The mixture was placed in a freeze dryer and dried for 24 h to obtain a MXene / WO3 / Au composite material. 10 mg of the obtained composite material was dispersed in 50 μL of deionized water and drop-casted onto a flexible nylon substrate using a pipette using the solid solution drop casting method and allowed to dry naturally.

[0037] (5) The prepared NO2 sensor was placed in a CGS-MT test platform, and a 1 ppm NO2 atmosphere was provided to the test platform through a dynamic gas distribution platform method. The sensor was connected to a four-probe test platform and detection was carried out using a resistance-time curve mode. Mathematical methods were used to convert the resistance-time change into a response change, and the sensitivity of the sensor was calculated to be 2.70.

[0038] The advantages of this embodiment are that the introduction of accordion-shaped MXene and Au nanoparticles effectively improves the conductivity of WO3, while the rich functional groups on its surface help to improve the gas sensing performance of WO3, making the sensitivity of the sensor 2.70. Example

[0039] A preparation method of an accordion-shaped MXene and one-dimensional WO3 nanorod nano self-reduction growth Au nanoparticle NO2 gas-sensitive composite material, the specific method is as follows: (1) The flexible nylon substrate was cut into a length of 15 mm and a width of 15 mm, and ultrasonically cleaned with deionized water, acetone, and ethanol in sequence, with an ultrasonic frequency of 40 kHz and an ultrasonic cleaning time of 10 min. The substrate was blown dry with nitrogen for 5 min, and then magnetron sputtering technology was used to sputter interdigital electrodes with a length of 10 mm and a width of 1 mm on the substrate through the engraved template, and the electrodes were set aside for use.

[0040] (2) 2 g of the precursor MAX phase was placed in a cylindrical polytetrafluoroethylene reactor with a lid and a 5 mm vent hole. Before adding the precursor material MAX phase, in order to prevent the reaction from being too violent when hydrofluoric acid (HF (38% in H2O)) is directly added and to solve the problem of incomplete acid etching. 20 mL of 12 mol / L hydrofluoric acid (HF (38% in H2O)) was first placed in an open-pore polytetrafluoroethylene reactor. Ice cubes were added to the constant temperature water bath to stabilize the liquid environment temperature at 5°C. The reactor was immersed in a constant temperature water bath and a magnetic stirrer was added. After stirring at 500 r / min for 5 minutes, the precursor MAX phase was divided into multiple portions and slowly added to the reactor in sequence. The constant temperature water bath was then set to 40°C and reacted for 36 h to prepare accordion-shaped MXene. After the reaction, the obtained suspension was placed in a centrifuge tube and washed with deionized water at 3500 rpm for multiple times until the pH was equal to 7, and then placed in a freeze dryer for freeze drying for 24 h.

[0041] (3) 1 g of sodium tungstate dihydrate (Na2WO4·2H2O) and 0.6 g of thioacetamide (CH3CSNH2) were placed in a beaker, 10 mL of deionized water was added, and the mixture was stirred under magnetic stirring at 500 r / min for 2 hours to obtain a stable dispersion. The dispersion was mixed and stirred in the beaker for 1 hour, and then 10 mg, 20 mg, 80 mg, 120 mg, and 160 mg of the prepared accordion-shaped MXene were stirred with the solution for 10 minutes. The pH was then titrated to 3 using 12 mol / L hydrochloric acid (Hcl (37% in H2O)), and the solution was placed in a polytetrafluoroethylene hydrothermal reactor and placed in an oven to react at 200 °C for 20 hours.

[0042] (4) 100 mg of freeze-dried MXene / WO3 powder was ultrasonically dispersed in 50 μL of deionized water at an ultrasonic frequency of 40 kHz for 0.5 h, and 30 μL of 0.1 mol / L -1 The tetrachloroauric acid (HAuCl4·3H2O) was subjected to self-reduction reaction for 5 min and then dried in a freeze dryer for 24 h to obtain the MXene / WO3 / Au composite material. 10 mg of the obtained composite material was dispersed in 50 μL of deionized water and drop-casted onto a flexible nylon substrate using a pipette using the solid solution drop casting method and allowed to dry naturally.

[0043] (5) The prepared NO2 sensor was placed in a CGS-MT test platform, and a 1 ppm NO2 atmosphere was provided to the test platform through a dynamic gas distribution platform method. The sensor was connected to a four-probe test platform and detected using a resistance-time curve mode. The resistance-time change was converted into a response change using a mathematical method. The sensitivities of the sensor were calculated to be 3.32, 3.97, 2.87, 2.75, and 2.62, respectively.

[0044] The advantages of Example 2 over Example 1 are that the introduction of accordion-shaped MXene and Au nanoparticles effectively improves the conductivity of WO3, and the rich functional groups on its surface help to improve the gas sensing performance of WO3. In addition, by changing the content of the added accordion-shaped MXene in step (3), and by using the sensor prepared by the preparation method, the sensitivity of the sensor is changed, so that the sensitivity of the sensor is 3.32, 3.97, 2.87, 2.75, and 2.62, respectively. The sensitivity shows a trend of first increasing and then decreasing. When the content of the added accordion-shaped MXene is 20 mg, the sensor sensitivity is the maximum value of 3.97, and then continues to increase the content of the added accordion-shaped MXene. The sensitivity begins to decrease, and finally the sensor sensitivity drops to 2.62 when the added amount is 160 mg.

[0045] Comparative Example 1 (1) The flexible nylon substrate was cut into pieces with a length of 15 mm and a width of 15 mm. The pieces were ultrasonically cleaned with deionized water, acetone, and ethanol, respectively, at an ultrasonic frequency of 40 kHz and for 10 min. The substrate was blown dry with nitrogen for 5 min, and then magnetron sputtering technology was used to sputter interdigital electrodes with a length of 10 mm and a width of 1 mm onto the substrate through the engraved template. The electrodes were set aside for later use.

[0046] (2) 2 g of the precursor MAX phase was placed in a cylindrical polytetrafluoroethylene reactor with a lid and a 5 mm vent hole. Before adding the precursor material MAX phase, in order to prevent the reaction from being too violent when hydrofluoric acid (HF (38% in H2O)) is directly added and to solve the problem of incomplete acid etching. 20 mL of 12 mol / L hydrofluoric acid (HF (38% in H2O)) was first placed in an open-pore polytetrafluoroethylene reactor. Ice cubes were added to the constant temperature water bath to stabilize the liquid environment temperature at 5°C. The reactor was immersed in a constant temperature water bath and a magnetic stirrer was added. After stirring at 500 r / min for 5 minutes, the precursor MAX phase was divided into multiple portions and slowly added to the reactor in sequence. The constant temperature water bath was then set to 40°C and reacted for 36 h to prepare accordion-shaped MXene. After the reaction, the obtained suspension was placed in a centrifuge tube and washed with deionized water at 3500 rpm for multiple times until the pH was equal to 7, and then placed in a freeze dryer for freeze drying for 24 h.

[0047] (3) 1 g of sodium tungstate dihydrate (Na2WO4·2H2O) and 0.6 g of thioacetamide (CH3CSNH2) were placed in a beaker, 10 mL of deionized water was added, and the mixture was stirred under magnetic stirring at 500 r / min for 2 hours to obtain a stable dispersion. The dispersion was mixed and stirred in the beaker for 1 hour, and 20 mg of the prepared accordion-shaped MXene was stirred with the solution for 10 minutes. The pH was then titrated to 3 using 12 mol / L hydrochloric acid (HCL (37% in H2O)), and the solution was placed in a polytetrafluoroethylene hydrothermal reactor and placed in an oven to react at 200 °C for 20 hours.

[0048] (4) Take 10 mg of freeze-dried powdered MXene / WO3 and disperse it in 50 μL of deionized water. Use a pipette to drop cast it onto a flexible nylon substrate using the solid solution drop casting method and let it dry naturally.

[0049] (5) The prepared NO2 sensor was placed in a CGS-MT test platform, and a 1 ppm NO2 atmosphere was provided to the test platform through a dynamic gas distribution platform method. The sensor was connected to a four-probe test platform and detection was carried out using a resistance-time curve mode. The resistance-time change was converted into a response change using a mathematical method, and the sensitivity of the sensor was calculated to be 2.54.

[0050] Comparative Example 2 (1) The flexible nylon substrate was cut into pieces with a length of 15 mm and a width of 15 mm. The pieces were ultrasonically cleaned with deionized water, acetone, and ethanol, respectively, at an ultrasonic frequency of 40 kHz and for 10 min. The substrate was blown dry with nitrogen for 5 min, and then magnetron sputtering technology was used to sputter interdigital electrodes with a length of 10 mm and a width of 1 mm onto the substrate through the engraved template. The electrodes were set aside for later use.

[0051] (2) 1 g of sodium tungstate dihydrate (Na2WO4·2H2O) and 0.6 g of thioacetamide (CH3CSNH2) were placed in a beaker, 10 mL of deionized water was added, and the mixture was stirred with magnetic stirring at 500 r / min for 2 hours to obtain a stable dispersion. The dispersion was mixed and stirred in the beaker for 1 hour, and then the pH was titrated to 3 using 12 mol / L hydrochloric acid (Hcl (37% in H2O)). The solution was placed in a polytetrafluoroethylene hydrothermal reactor and placed in an oven for reaction at 200 °C for 20 hours.

[0052] (3) 100 mg of freeze-dried powdered 1D WO3 nanorods were ultrasonically dispersed in 50 μL of deionized water, drop-casted onto a flexible nylon substrate using a solid solution drop casting method using a pipette and allowed to dry naturally.

[0053] (4) The prepared NO2 sensor was placed in a CGS-MT test platform, and a 1 ppm NO2 atmosphere was provided to the test platform through a dynamic gas distribution platform method. The sensor was connected to a four-probe test platform and detection was carried out using a resistance-time curve mode. Mathematical methods were used to convert the resistance-time change into a response change, and the sensitivity of the sensor was calculated to be 1.85.

[0054] Experimental testing The sensors prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were connected to the CGS-MT four-probe dynamic test platform and tested in real time using the resistance-time curve mode. The resistance-time change was converted into the response change using mathematical methods, and the sensitivity of 1 ppm NO2 was tested. The results are as follows: Figure 4 As shown, the accordion-shaped MXeneTi3C2T x The addition of MXene can effectively improve the sensitivity of one-dimensional WO3 nanorod gas-sensitive materials.

[0055] Figure 5 The sensitivity of the MXene / WO3 / Au composite gas-sensitive material first increases and then decreases. When the MXene addition amount is 20 mg, it has the highest sensitivity of 3.97 to 1 ppm NO2 at room temperature.

[0056] The sensor prepared in Example 3 was connected to the CGS-MT four-probe dynamic test platform and tested in real time using the resistance-time curve mode. The resistance-time change was converted into the response change using mathematical methods. The sensitivity of 100 ppb~1ppm NO2 was tested. The results are as follows: Figure 4 As shown, the response of the sensor prepared based on the composite gas-sensitive material at 100ppb~1 ppm gradually increases with the increase of NO2 concentration, and is higher than the response of the sensor prepared based on the one-dimensional WO3 nanorod material in comparative example 2 and the sensor prepared based on MXene / WO3 in comparative example 1 at the corresponding concentration.

[0057] The MXene / WO3 / Au composite gas-sensitive material prepared in Example 3 was subjected to SEM to obtain Figure 1. Figure 1 As shown, MXene Ti3C2T x It has an obvious accordion-like structure, and the one-dimensional WO3 nanorods and Au nanoparticles are tightly and evenly distributed in the MXene Ti3C2T x surface and between layers.

[0058] The present invention adopts the MXene / WO3 prepared in Comparative Example 1 to obtain the SEM Figure 2 , one-dimensional WO3 nanorods are evenly distributed on the surface and in the MXene layer, The present invention adopts the one-dimensional WO3 nanorods prepared in Comparative Example 2 to obtain the SEM Figure 3 ,like Figure 3 As shown, the average diameter of one-dimensional WO3 nanorods is about 80 nm.

[0059] The above embodiments provide a detailed introduction to the products and methods of the present invention. Specific examples are used herein to illustrate the main steps and implementation methods of the present invention. The above embodiments are only to help understand the methods and core principles of the present invention. For those skilled in the art, according to the core principles of the present invention, various conditions and parameters may be changed as needed in specific implementations. In summary, this specification should not be construed as limiting the present invention.

Claims

1. A method for preparing an organ-shaped MXene and one-dimensional WO3 nanorod nano self-reduction growth Au nanoparticle NO2 gas-sensitive composite material, characterized in that: The specific steps are as follows: Step (1), preparation of a polymer flexible substrate: a flexible nylon substrate is cut into pieces with a length of 15 mm and a width of 15 mm, and ultrasonically cleaned with deionized water, acetone and ethanol in sequence, with an ultrasonic frequency of 30 to 50 KHz and an ultrasonic cleaning time of 5 to 15 min. The substrate is blown dry with nitrogen, and then a magnetron sputtering technique is used to sputter interdigital electrodes with a length of 10 mm and a width of 1 mm onto the substrate through an engraved template, and the electrodes are set aside for use; Step (2), preparation of accordion-shaped MXene: 1-2 g of the precursor MAX phase is placed in a cylindrical reactor with a lid made of polytetrafluoroethylene. In order to remove the H2 produced during the reaction, which may cause safety hazards, a 5 mm diameter exhaust hole is opened at 1 cm from the top of the reactor using a punching machine. Before adding the precursor material MAX phase, in order to prevent the reaction from being too violent when hydrofluoric acid (HF (38% in H2O)) is directly added and to solve the problem of incomplete acid etching. Place 20-40 mL of 3-12 mol / L hydrofluoric acid (HF (38% in H2O)) in a perforated polytetrafluoroethylene reactor, add ice cubes to a constant temperature water bath to stabilize the liquid environment temperature at 0-10 °C, immerse the reactor in a constant temperature water bath, add a magnetic stirrer, stir at 500 r / min-1000 r / min for 1-10 minutes, divide the precursor MAX phase into multiple portions, slowly add them to the reactor in sequence, set the constant temperature water bath to 30-60 °C, react for 12-48 h, and prepare the accordion-shaped MXene. After the reaction, place the obtained suspension in a centrifuge tube and use deionized water to centrifuge and wash it multiple times at 3500 rpm-10000 rpm until the pH is equal to 7, and then freeze-dry in a freeze dryer for 24-48 h. Step (3), preparation of MXene / WO3 composite material: 0.1-2 g sodium tungstate dihydrate (Na2WO4·2H2O) and 0.1-2 g thioacetamide (CH3CSNH2) are placed in a beaker, deionized water is added, and magnetic stirring is performed at 500 r / min-1000 r / min for 2 hours to obtain a stable dispersion. The dispersion is mixed and stirred in the beaker for 1 hour, and the accordion-shaped MXene prepared in step (2) is stirred with the solution for 10 minutes, wherein the mass percentage of the added accordion-shaped MXene is 5.0-20 wt%, and then 3-12 mol / L hydrochloric acid (Hcl (37% in H2O)) is used to titrate the pH to 2-5, and then the solution is placed in a hydrothermal reactor made of polytetrafluoroethylene and placed in an oven to react at 100-200°C for 10-20 hours; Step (4), preparation of MXene / WO3 / Au composite material: After the reaction is completed, the suspension obtained in step (3) is placed in a centrifuge tube and repeatedly centrifuged and washed with deionized water at 3500 rpm~10000 rpm, and then placed in a freeze dryer for freeze drying for 24 h~48 h to obtain a MXene / WO3 composite material. 10-100 mg of freeze-dried powder MXene / WO3 was ultrasonically dispersed in 50-100 μL deionized water at an ultrasonic frequency of 30-50 KHz for 0.5-1.5 h. 0.01-1 mL of 0.1 mol / L tetrachloroauric acid (HAuCl4·3H2O) was slowly added dropwise for self-reduction reaction for 5-60 min. The mixture was placed in a freeze dryer and dried for 12-48 h to obtain a MXene / WO3 / Au composite material. 5-20 mg of the composite material obtained in step (4) was dispersed in 50-200 μL deionized water. The mixture was drop-casted onto the substrate obtained in step (1) using a pipette using a solid solution drop casting method and allowed to dry naturally.

2. According to the preparation method of the accordion-shaped MXene and one-dimensional WO3 nanorod nano self-reduction growth Au nanoparticle NO2 gas-sensitive composite material according to claim 1, the centrifugal speed of the preparation of the MXene / WO3 / Au composite material in the step (4) is 3500 rpm, the freeze-drying time is 24 h, the amount of the freeze-dried powder MXene / WO3 added is 100 mg and dispersed in 100 mL of deionized water, ultrasonically dispersed at an ultrasonic frequency of 40 KHz for 0.5 h, 0.03 mL of 0.1 mol / L tetrachloroauric acid (HAuCl4·3H2O) is slowly added dropwise, the self-reduction reaction is 5 min, and the mixture is placed in a freeze dryer for freeze drying for 24 h, 10 mg of the MXene / WO3 / Au composite material is dispersed in 50 μL of deionized water, transferred to the flexible substrate obtained in step (1), and naturally dried for 24 h.

3. According to the method for preparing a accordion-shaped MXene and one-dimensional WO3 nanorod nano self-reduction growth Au nanoparticle NO2 gas-sensitive composite material according to claim 1, in the preparation of the MXene / WO3 composite material in step (3), sodium tungstate dihydrate (Na2WO4·2H2O) and thioacetamide (CH3CSNH2) accordion-shaped MXene, the added amount of sodium tungstate dihydrate (Na2WO4·2H2O) is 1 g, thioacetamide (CH3CSNH2) is 0.6 g, and the added mass of the accordion-shaped MXene is 20 mg.

4. According to the method for preparing a accordion-shaped MXene and one-dimensional WO3 nanorod nano-self-reduction-grown Au nanoparticle NO2 gas-sensitive composite material according to claim 1, the accordion-shaped MXene added in step (3) is one of Ti3C2, Ti2C, Nb3C4, Nb2C, V3C2, V2C, Ta4C3, Ta2C and Mo2C.

5. According to the method for preparing the accordion-shaped MXene and one-dimensional WO3 nanorod nano-self-reduction-grown Au nanoparticle NO2 gas-sensitive composite material according to claim 1, the step (3) slowly titrates 12 mol / L hydrochloric acid (Hcl (37% in H2O)) until the pH value of the solution reaches 3.

6. According to the method for preparing an accordion-shaped MXene and one-dimensional WO3 nanorod nano-self-reduction-grown Au nanoparticle NO2 gas-sensitive composite material as described in claim 1, in the step (3), a hydrothermal reactor made of polytetrafluoroethylene is placed in an oven and reacted at 200°C for 20 hours.

7. According to the method for preparing an accordion-shaped MXene and one-dimensional WO3 nanorod nano-self-reduction-grown Au nanoparticle NO2 gas-sensitive composite material according to claim 1, the MAX phase material in step (2) is one of Ti3AlC2, Ti2AlC, Nb3AlC4, Nb2AlC, V3AlC2, V2AlC, Ta4AlC3, Ta2AlC and Mo2AlC.

8. The method for preparing a accordion-shaped MXene and one-dimensional WO3 nanorod nano-self-reduction-grown Au nanoparticle NO2 gas-sensitive composite material according to claim 1, wherein in the step (2), 2 g of the MAX phase material is slowly added multiple times and dissolved in 40 mL of 3-12 mol / L hydrofluoric acid (HF (38% in H2O)), and a constant temperature water bath is set at 40°C for reaction for 36 hours. After the reaction, the obtained suspension is placed in a centrifuge tube and centrifuged and washed multiple times with deionized water at 3500 rpm until the pH is equal to 7, and then placed in a freeze dryer for freeze drying for 24 hours.

9. According to the method for preparing an accordion-shaped MXene and one-dimensional WO3 nanorod nano-self-reduction-grown Au nanoparticle NO2 gas-sensitive composite material as described in claim 1, before adding the MAX phase material to HF, the step (2) stabilizes the liquid environment temperature at 5°C by adding ice cubes to a constant temperature water bath, immerses the reactor in a constant temperature water bath, adds a magnetic stirrer, and stirs at 500 r / min for 5 minutes.

10. The method for preparing an accordion-shaped MXene and one-dimensional WO3 nanorod nano-self-reduction-grown Au nanoparticle NO2 gas-sensitive composite material according to claim 1, wherein the nylon substrate is cut into a length of 15 mm and a width of 15 mm, and the ultrasonic washing is performed at an ultrasonic frequency of 40 KHz for 10 min. After the substrate is dried with nitrogen for 5 min, a magnetron sputtering technique is used to sputter an interdigitated electrode with a length of 10 mm and a width of 1 mm onto the substrate through an engraved template, and the electrode is set aside for use.

Citation Information

Cited By

  • Gas-sensitive material based on tungsten trioxide modified single-layer V2CTx nanosheet as well as preparation method and application of gas-sensitive material

    CN121164375A